2020
DOI: 10.1021/acs.jafc.9b07555
|View full text |Cite
|
Sign up to set email alerts
|

Allicin Modifies the Composition and Function of the Gut Microbiota in Alcoholic Hepatic Steatosis Mice

Abstract: The intestinal microbiome plays an important role in the pathogenesis of liver diseases. Alcohol intake induces gut microbiota dysbiosis and alters its function. This study investigated the antibiotic effect of allicin in mice with hepatic steatosis. Male C57BL/6 mice were administered an ethanol diet supplemented with allicin (5 and 20 mg/(kg bw day)) for 4 weeks. Allicin modified the gut microbiota composition. Cecal microbiota exhibited a positive correlation with alcohol and hepatic triacylglycerol, but we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 63 publications
(126 reference statements)
1
21
0
1
Order By: Relevance
“…Curcumin processed a variety of bioactivities such as antioxidant, anti-inflammatory, and hepatoprotective effects, and a systematic review and dose-response meta-analysis of randomized controlled trials demonstrated that curcumin could ameliorate visceral fat and abdominal obesity in NAFLD patients [60]. Allicin (diallyl thiosulfonate), a bioactive component from the aqueous extracts of garlic, could decrease the abundance of gut microbiota, like Christensenellaceae and Ruminococcaceae, in alcoholic hepatic steatosis mice, resulting in a reduction of hepatic triacylglycerol level [61,62].…”
Section: Beneficial Bioactivementioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin processed a variety of bioactivities such as antioxidant, anti-inflammatory, and hepatoprotective effects, and a systematic review and dose-response meta-analysis of randomized controlled trials demonstrated that curcumin could ameliorate visceral fat and abdominal obesity in NAFLD patients [60]. Allicin (diallyl thiosulfonate), a bioactive component from the aqueous extracts of garlic, could decrease the abundance of gut microbiota, like Christensenellaceae and Ruminococcaceae, in alcoholic hepatic steatosis mice, resulting in a reduction of hepatic triacylglycerol level [61,62].…”
Section: Beneficial Bioactivementioning
confidence: 99%
“…Collectively, spices like onion and curcumin from turmeric could prevent NAFLD through improving lipid metabolism, oxidative stress, and inflammation (Table 1) 9 Oxidative Medicine and Cellular Longevity [107]. Also, allicin could alleviate alcohol-induced hepatic steatosis in C57BL/6 mice by modifying gut dysbiosis and then reducing the production of lipopolysaccharide (LPS) and further inhibiting TLR4-mediated inflammation [62]. Besides, the consumption of the ginger extract could significantly regulate lipid homeostasis in Wistar rats by increasing the expression of hepatocyte nuclear factor 4 α gene (HNF4A), while decreasing the expression of the protein tyrosine phosphatase 1B gene (PTP1B) [108,148].…”
Section: Mechanisms Of Spices and Their Bioactive Compounds On Nafldmentioning
confidence: 99%
“…Allicin, ethanol extracts of bitter gourd, and lychee exhibited anti-inflammatory effects against AFLD. In addition, allicin 72 and lychee have been shown to suppress the LPS-CD14-toll-like receptor 4 pathway, and modulate intestinal microbiota dysbiosis and intestinal barrier dysfunction. 73 …”
Section: Chinese Herbs and Fatty Liver Diseasementioning
confidence: 99%
“…Alcohol consumption could cause the imbalance of gut microflora and destroy the homeostasis of bile acid metabolism. Recently, the critical role of gut microflora and bile acids in ALD has been demonstrated (Hartmann et al., 2018; Panyod et al., 2020). Moreover, Wahlstrom et al (Wahlström et al., 2017) have confirmed the concept of gut microflora‐bile acid axis.…”
Section: Introductionmentioning
confidence: 99%